2018
DOI: 10.1016/j.socscimed.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The geography of smallpox in England before vaccination: A conundrum resolved

Abstract: Smallpox is regarded as an ancient and lethal disease of humans, however very little is known about the prevalence and impact of smallpox before the advent of vaccination (c.1800). Here we use evidence from English burial records covering the period 1650–1799 to confirm a striking geography to smallpox patterns. Smallpox apparently circulated as a childhood disease in northern England and Sweden, even where population densities were low and settlement patterns dispersed. However, smallpox was a relatively rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…A possible explanation for these phenomena, of a widening and subsequent narrowing of survival differentials by familial wealth in the period 1752-1812, is changes in the availability of prophylactics against smallpox. Smallpox was the leading cause of child mortality in eighteenth-century cities (Davenport, Boulton, & Schwarz, 2016;Davenport, Satchell, & Shaw-Taylor, 2018;Landers, 1993, Mercer, 2014, and Landers demonstrated that the large improvements in post-neonatal and child mortality of London Quakers in the second half of the eighteenth century were driven mainly by a specific reduction in smallpox mortality (although smallpox could not account fully for the fall in mortality in post-neonatal infants). Two forms of immunisation against smallpox became available in England in the course of the eighteenth century.…”
Section: Mortality In the First Two Years Of Life By Familial Wealthmentioning
confidence: 99%
“…A possible explanation for these phenomena, of a widening and subsequent narrowing of survival differentials by familial wealth in the period 1752-1812, is changes in the availability of prophylactics against smallpox. Smallpox was the leading cause of child mortality in eighteenth-century cities (Davenport, Boulton, & Schwarz, 2016;Davenport, Satchell, & Shaw-Taylor, 2018;Landers, 1993, Mercer, 2014, and Landers demonstrated that the large improvements in post-neonatal and child mortality of London Quakers in the second half of the eighteenth century were driven mainly by a specific reduction in smallpox mortality (although smallpox could not account fully for the fall in mortality in post-neonatal infants). Two forms of immunisation against smallpox became available in England in the course of the eighteenth century.…”
Section: Mortality In the First Two Years Of Life By Familial Wealthmentioning
confidence: 99%
“…Sir, Smallpox was one of the most lethal human pathogens in history. 1 It originated around 10,000 years before common era (BCE) in North-eastern Africa, and spread world-wide through human migration and increasing population densities with periodic epidemics throughout the world. 2 By the middle of the 18 th century, around one million Europeans each year were contracting the disease with approximately one third of adults and 90 percent of infants succumbing to it.…”
Section: Smallpox: Leaving Its Mark On Public Healthmentioning
confidence: 99%
“…11 In England, infected individuals were restricted by local authorities to stay within their households, markets were closed and pest houses (originally used for plague epidemics) were used during smallpox outbreaks. 1 Another preventative measure centred around inducing immunity in individuals artificially. It was known, from as early as the 5 th century BCE, that people previously infected with smallpox were immune from re-infection.…”
Section: Smallpox: Leaving Its Mark On Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a vaccine developed by Edward Jenner at the end of 18th century, smallpox accounted for some 10-15 million cases annually until 1967. In 1980, the disease was considered eradicated after a successful global vaccination program [33][34][35]. Some pathogens are considered as potential candidates for use in armed conflicts as biological warfare agents.…”
Section: Introductionmentioning
confidence: 99%